Impact on energy efficiency by type of photometric curve in warehouse lighting projects - Chacaliaza Huapaya, Luis Aurelio (2023)
The objective of this work is to demonstrate the need to carry out lighting studies for an efficient use of energy consumption through the appropriate choice of luminaires and their photometric distribution, and the benefits obtained as a result of an optimal lighting study. Due to the increasing importance of optimized lighting, it is important to show that the results can be further optimized. The analysis shows the results of software simulations with metal halide lamp luminaires and the LED equivalent. For the lighting of narrow areas, which is common in warehouses, it is taken as a case study the warehouses with racks and narrow aisles, the use of lighting in very important, having warehouses that can work 24 hours a day and 07 days a week. The vast majority of this type of facilities maintain the use of metal halide and the conventional optimization proposal is the change to LED, with which you get to have significant energy savings. However, the industry has not taken into account the need to choose the appropriate photometric distribution for the type of area to be illuminated, luminaires of the same light source technology can be used, but with different types of photometric distribution and, with a correct lighting study, 84% less installed power and 50% less luminaires with metal halide lamp compared to an installation with LED, in the study three types of photometric distribution are presented, performing calculations in Dialux 4.13  software showing how these results have an impact on the number of luminaires to be used, the installed power and, consequently, the expenses derived from installation, operation and maintenance. This optimization of resources results in less pollution due to greenhouse gas (GHG) emissions.